Nach Corona kommt die Schuldenwelle – begründete Sorge oder Panikmache? Aktuelle Entwicklungen im Kredit- und Konsummarkt; After corona comes the debt waveswell-founded concern or scaremongering? - Kai-Friedrich Donau (Wirtschaftsdienst, 2022)
– The corona pandemic had a considerable impact on consumers. The difficult situation in numerous sectors of the economy has led to financial burdens for many households. Despite repeated warnings announcing significantly increasing debts, the number of new payment arrears during the past two years has been below the level of the pre-COVID-19 period according to analysis based on SCHUFA data. This is due to the fact that consumers have adjusted their financial and consumption behavior or made use of their financial reserves - reserves that could now be lacking due to rising prices, especially for energy.
Keywords: E21; G51; G53; 330; Private Verschuldung; Deutschland